Fritha' s summer - Morris, Susan (MPress Book, 2009)
Set in the west of England during the summer holidays, Fritha and her brothers live on safe, ordinary Harebell Road. Their adventure begins when their mother takes them away. They find themselves living in a derelict caravan in Cornwall and life isn't safe or ordinary any more. Meeting a strange, foreign boy leads Fritha to hidden treasure, danger, and the answer to a family secret.